SHUTTING THE STABLE DOOR AFTER THE HORSE HAS BOLTED. - Niklasson, Elisabeth (Current Swedish Archaeology / Svenska Arkeologiska Samfundet, 2014)
The article discusses aspects of the diagnostic statements about discipline within archaeology. It highlights the post-modernist discourse analysis of new types and levels of data input in the evolutionary system approaches of technology. It also cites the availability of scientific data that focus on quantification and agent-based modelling methodologies.